Influence of Inventory Turnover, Receivable Turnover, and Sales Growth on Profitability with Good Corporate Governance as a Moderating Variable: Companies with Trading and Distribution Business Sectors Listed on the Indonesian Stock Exchange for 2020 - 2022 Period - Fatmawati, Fatmawati; Wiralestari, Wiralestari; Hernando, Riski (PT. Riset Press International, 2024)
This research aims to examine and analyze the influence of inventory turnover, receivable turnover and sales growth partially and simultaneously on ROA in trading and distribution business companies listed on the Indonesia Stock Exchange. The population in this research are trading and distribution business companies listed on the Indonesia Stock Exchange. The sampling technique used in this research was the purposive sampling method and 12 companies were obtained. The analysis technique in this research uses multiple linear regression analysis techniques and Moderated Regression Analysis (MRA) using the SPSS 29 program. The results of this research conclude that inventory turnover has an effect on profitability while receivable turnover and sales growth have no effect on profitability. While the Independent Board of Commissioners can significantly influence the relationship between inventory turnover and profitability, the Independent Board of Commissioners cannot influence or is unable to moderate the relationship between receivable turnover and sales growth and profitability.